EFFECTIVENESS OF YOGA CHILD POSE ON ALLEVIATING MENSTRUAL PAININ FEMALE ADOLESCENTS - Meda Yuliani; Ina Sugiharti; Intan Yusita; Iceu Mulyati; Siska Nurul Agustiani (Jurnal Kesehatan Kusuma Husada, 2025)
Background: Menstrual pain, or dysmenorrhea, arises from heightened prostaglandin production, leading to uterine cramps. This discomfort can interfere with daily activities. One recommended non-pharmacological approach to relieve this condition is practising the child's pose in yoga. This study aims to assess the effectiveness of this pose in reducing menstrual discomfort among students. Methods: The research was conducted at SMPN 2 Pamulihan during the period of July through August. This study employed a pre-experimental design with a one-group pretest-posttest approach. The participants were 7th and 8th grade junior high school students experiencing primary dysmenorrhea who met the inclusion and exclusion criteria. Pain assessment was conducted using the Numeric Rating Scale (NRS), a validated and widely accepted instrument for evaluating pain levels. The yoga intervention was implemented based on established Standard Operating Procedures (SOP) to ensure consistency and adherence to protocol. Data were analysed using univariate and bivariate analyses, with the Wilcoxon test applied to assess the differences between pretest and posttest results. Results: Prior to the intervention, 25 participants (69.4%) experienced mild pain. Following the yoga sessions, 26 students (72.2%) reported mild pain. Statistical analysis revealed a significant difference before and after the intervention (p = 0.000 < 0.05), indicating the potential of child's pose yoga as a non-pharmacological method for easing dysmenorrhea. Conclusion: The child's pose yoga technique shows promise in managing menstrual discomfort among adolescents, serving as a viable non-pharmacological alternative.